2015
DOI: 10.1111/soc4.12240
|View full text |Cite
|
Sign up to set email alerts
|

The Only Thing We Have to Fear Is Fear Itself…and Crime: The Current State of the Fear of Crime Literature and Where It Should Go Next

Abstract: Researchers have explored the impact of fear of crime for well over 40 years. In that time, the fear of crime literature has undergone a remarkable evolution, with researchers examining it among varied populations, in many contexts, and from different theoretical perspectives. The purpose of the current work is to provide a brief review of the fear of crime literature, with specific focus on how the research has evolved. Particular attention is placed on how the definitions and measures of fear of crime have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 90 publications
1
58
1
4
Order By: Relevance
“…This has been supported by a small but growing body of evidence that connects experience of harassment with fear of crime (Macmillan, Nierobisz, and Welsh 2000;Davidson et al 2016). In turn, fear of sexual assault has been found to heavily influence womens fear of crime (May, Rader, and Goodrum 2010;Henson and Reyns 2015). While the relationship between fear of crime and fear of sexual assault is well established, the relationship between harassment, fear of sexual assault and overall fear of crime is in its infancy.…”
Section: Fear Of Crime and (Sexual) Harassmentmentioning
confidence: 92%
See 1 more Smart Citation
“…This has been supported by a small but growing body of evidence that connects experience of harassment with fear of crime (Macmillan, Nierobisz, and Welsh 2000;Davidson et al 2016). In turn, fear of sexual assault has been found to heavily influence womens fear of crime (May, Rader, and Goodrum 2010;Henson and Reyns 2015). While the relationship between fear of crime and fear of sexual assault is well established, the relationship between harassment, fear of sexual assault and overall fear of crime is in its infancy.…”
Section: Fear Of Crime and (Sexual) Harassmentmentioning
confidence: 92%
“…Research into crime, fear of crime and public transport has shown two seemingly incongruous results: while men are more likely to be the victim of crime on public transport (Smith 2008 . Accordingly, the strongest predictor of fear of crime is gender (Henson and Reyns 2015). While this appears contradictory, some scholars argue that womens fear of crime is in actuality fear of sexual crime (Hsu 2011), of which women are victimised more than men, and which is acknowledged to be vastly under-reported.…”
Section: Fear Of Crime and (Sexual) Harassmentmentioning
confidence: 95%
“…(Responses ranged from 0 = never to 4 = often.) Fear of Victimization is a mean rating scale based on responses to the six items listed in Table 1 (Gainey et al 2011;Henson and Reyns 2015). Fear of Crime is based on responses to ''I worry that crime in the United States is increasing.''…”
Section: Methodsmentioning
confidence: 99%
“…Generally, fear of crime can be defined as an emotional response to a danger or threat of an actual or potential criminal incident, whereas perceived risk may be seen as a cognitive response resulting from an assessment of the likelihood of being victimised (Henson & Reyns, 2015). However, these concepts share a considerable overlap, and the relationship between fear of crime and perceived risk has been suggested to be causal as well as reciprocal (Hicks & Brown, 2013).…”
Section: Introductionmentioning
confidence: 99%